Workshop Pemanfaatan Softwer Mendeley Bagi Dosen STAI Hasan Jufri Bawean - Sholihan; Ansharuddin M (LP3M IAIFA Kediri, 2024)
Mendeley, as one of the popular reference management software, offers various conveniences in storing, organizing, and inserting references into scientific documents. However, limited understanding and skills in using Mendeley are still an obstacle faced by many people, especially students and lecturers who are not familiar with digital technology. Through Mendeley utilization training, participants are expected to improve their ability to manage references more effectively and efficiently. This community service also aims to support the improvement of the quality of scientific work, both in terms of technical and substance. the method used in this research is the service learning method with the following steps first Identification of Problems and Needs second Provision of Material and Simulation third Collaboration and Experience-Based Reflection fourth Application in Real Context fifth fifth Evaluation and feedback. While the results of this activity can have a positive impact including increasing understanding of mendeley, Application in Academic Activities. Efficiency in Reference Preparation Establishment of Digital Literacy Culture Collaboration between Lecturers Translated with DeepL.com (free version)